2005
DOI: 10.1128/aem.71.4.1915-1922.2005
|View full text |Cite
|
Sign up to set email alerts
|

Formation of trans Fatty Acids Is Not Involved in Growth-Linked Membrane Adaptation of Pseudomonas putida

Abstract: Fatty acid compositions in growing and resting cells of several strains of Pseudomonas putida (P8, NCTC 10936, and KT 2440) were studied, with a focus on alterations of the saturation degree, cis-trans isomerization, and cyclopropane formation. The fatty acid compositions of the strains were very similar under comparable growth conditions, but surprisingly, and contrary to earlier reports, trans fatty acids were not found in either exponentially growing cells or stationary-phase cells. During the transition fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 62 publications
(53 reference statements)
4
69
1
6
Order By: Relevance
“…Martin and Jenkins (2002) and Pottier et al (2006), however, suggested that vitamin E might have inhibitory and stimulatory effects on the growth and function of bacteria that produce t10-and t11-18:1, respectively. Given that ruminal environmental stress is an important factor for the synthesis of trans fatty acids in the rumen (Hä rtig et al, 2005), vitamin E may in some way alleviate this stress, although it may not be through its typical role as an anti-oxidant, given the highly reduced environment of the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…Martin and Jenkins (2002) and Pottier et al (2006), however, suggested that vitamin E might have inhibitory and stimulatory effects on the growth and function of bacteria that produce t10-and t11-18:1, respectively. Given that ruminal environmental stress is an important factor for the synthesis of trans fatty acids in the rumen (Hä rtig et al, 2005), vitamin E may in some way alleviate this stress, although it may not be through its typical role as an anti-oxidant, given the highly reduced environment of the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…Изменение состава фосфолипидов является эволюционным ответом микроорганизмов на физические и химические изменения в окру-жающей среде, своеобразной адаптацией, ко-торая включается в период роста бактерий [8,9,10]. Однако механизмы гомеофазовой адап-тации у разных микроорганизмов отличаются.…”
Section: Discussionunclassified
“…Однако механизмы гомеофазовой адап-тации у разных микроорганизмов отличаются. Преобладающей реакцией многих бактерий на внешние воздействия является модификация ацильной цепи липидных структур за счет из-менения соотношения насыщенных и ненасы-щенных жирных кислот [2,10]. Также описа-ны механизмы сокращения или удлинения це-пи, изменения в соотношении разветвленных жирных кислот, рост-зависимое метилирова-ние или насыщение циклопропаном, а также цис-транс-изомеризационное преобразова-ние двойных связей (π -диастереометрия) [3,14].…”
Section: Discussionunclassified
See 2 more Smart Citations